(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Anterior open bite associated with class II malocclusion and a vertical growth pattern is difficult to treat in adult patients. Orthodontic camouflage with miniscrew anchorage may serve as a less invasive alternative to orthognathic surgery in selected cases. Case presentation: A 22-year-old woman presented with maxillary protrusion and anterior open bite. Clinical examination revealed a convex profile, retruded chin, tongue-thrust and mouth-breathing habits, a constricted maxillary arch, an anterior open bite with an overbite of -5 mm and an overjet of 5 mm. Ricketts analysis demonstrated a Class II skeletal discrepancy. Intervention and outcome: The patient underwent orthodontic camouflage treatment using Damon self-ligating brackets, extraction of teeth 16 and 26, maxillary molar intrusion combined with extrusion and retraction of the maxillary incisors supported by miniscrew anchorage. After 28 months, an overbite and overjet of 1.5 mm, bilateral class I canine relationships, and improved facial esthetics were achieved. Conclusion: Orthodontic camouflage with miniscrew anchorage can provide favorable functional and esthetic outcomes in patients with anterior open bite associated with class II malocclusion without the need for surgery.